2023
DOI: 10.3390/s23031541
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Species Cover Crop Biomass Estimation Using Planet Imagery

Abstract: Cover crop biomass is helpful for weed and pest control, soil erosion control, nutrient recycling, and overall soil health and crop productivity improvement. These benefits may vary based on cover crop species and their biomass. There is growing interest in the agricultural sector of using remotely sensed imagery to estimate cover crop biomass. Four small plot study sites located at the United States Department of Agriculture Agricultural Research Service, Crop Production Systems Research Unit farm, Stoneville… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Despite test accuracy and F1 scores both exceeding 0.78, the random forest models trained on three years of PlanetScope and SkySat data performed poorly at classifying high incidence GDM for images acquired during advanced disease stages in 2021 and 2022 (Figure 5). In a comparison of PlanetScope VIs for cover crop yield estimation, Kharel et al also found that NDVI was positively correlated with biomass across their study period, supporting the link between NDVI and amount of healthy vegetation (Kharel et al 2023). Further, they observed that correlation coefficients between biomass, VIs, and spectral bands depended on the time of image acquisition, with highest correlation observed at late vegetative growth stages.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Despite test accuracy and F1 scores both exceeding 0.78, the random forest models trained on three years of PlanetScope and SkySat data performed poorly at classifying high incidence GDM for images acquired during advanced disease stages in 2021 and 2022 (Figure 5). In a comparison of PlanetScope VIs for cover crop yield estimation, Kharel et al also found that NDVI was positively correlated with biomass across their study period, supporting the link between NDVI and amount of healthy vegetation (Kharel et al 2023). Further, they observed that correlation coefficients between biomass, VIs, and spectral bands depended on the time of image acquisition, with highest correlation observed at late vegetative growth stages.…”
Section: Discussionmentioning
confidence: 78%
“…The proliferation of the commercial high resolution Earth observation industry has reinvigorated research interest in spaceborne ecological surveillance. SkySat and PlanetScope imagery has been used for a range of ecosystem and agricultural applications, including biomass estimation, vegetation classification, plant disease detection, quantifying evapotranspiration, and soil moisture mapping (Kharel et al 2023; Guo et al 2022; Szabó et al 2021; Shi et al 2018; Baloloy et al 2018; Du et al 2022; Raza et al 2020; Aragon et al 2021). The frequent revisit times and fine spatial scale of these platforms enables monitoring diverse specialty crops, including grapevine, despite their smaller, spatially heterogeneous fields (Helman et al 2018; Meyers et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Of the many space‐based sensors to choose from, PlanetScope was selected because it has high spatial (3.12 m × 3.12 m) and temporal (daily) resolution and provides multispectral images (blue [455–515 nm], green [500–590 nm], red [590–670 nm], and near‐infrared [780–860 nm]; Jain et al., 2016; Planet Team, 2017; Yang et al., 2012). The Ortho Scene‐Analytics (Level 3B) surface reflectance imageries are orthorectified, radiometrically calibrated, and atmospherically corrected products that capture the reflectance characteristics of the lower atmosphere (Frazier & Hemingway, 2021; Houborg & McCabe, 2018; T. P. Kharel et al., 2023). Between planting and harvesting in 2019 and 2021, six cloud‐free images at six growth stages (VE/VC [June 10]; V1/V3 [July 2], R1/R2 [July 24], and R2/R3 [August 10], R4/R5 [August 25], and R6/R7 [September 10]) were acquired.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have focused on the exploitation of remote sensing data and indices for use in constructing mathematical models for forecasting maize silage yield. [5][6][7][8][9][10][11][12] Two examples of vegetation indices (VIs) that have shown promise as predictors are the normalized difference vegetative index (NDVI) and enhanced vegetative index (EVI). Both indices are regularly used in linear and exponential regression models:…”
Section: Remote Sensing Based Yield Forecast Modelsmentioning
confidence: 99%
“…The National Aeronautics and Space Administration's (NASA) Landsat and Moderate Resolution Imaging Spectroradiometer (MODIS) imagery systems, Planet Labs' Dove and Superdove constellations, and the European Space Agency's (ESA) Sentinel satellites provide calibrated reflectance imagery which have been used for such yield predictions. [5][6][7][8] Recent advances in machine learning have created new opportunities for spectral data exploitation, using neural networks to perform regression analysis on imagery instead of traditional least squares regressions. However, machine learning regression performance benefits from more information than is available in the multispectral systems previously mentioned.…”
Section: Remote Sensing Based Yield Forecast Modelsmentioning
confidence: 99%